Mulheres negras e suas representações nas coleções de livros didáticos de Biologia aprovados pelo PNLD – 2015 - Silva, Lauana Araújo (2018)
The following study considered the biology textbooks as cultural items that are social, spatial and temporally located. For this reason, based on the theoretical perspective from the fields of education, cultural studies, genre studies, feminism studies and on the Ethnic-racial relations, the research understands that textbooks carry aspects of class, genre, race and ethnicity on them. Since the economic, cultural, educational and symbolic power, historically unfeasible the plurality of black women, the study aimed to reflect on the production of meanings from the representation of black women in biology textbooks and on their contribution of the knowledge produced about ethnic-racial relations. The methodology used in the research was the interpretative-descriptive, in which the main goal was to analyze the social-cultural meanings produced from the images of black women in Biology textbooks. The specific goals of this research were to identify the images of black women in the 27 Biology collections approved by the Textbooks National Program (Programa Nacional do Livro Didático – PNLD) in 2015; to indicate the themes, contents and subjects that the images of black women were related to, analyzing the ideas associated to these images. On the analysis, based on the descriptive-interpretative approach, it was found images of black women associated to the maternity and biological processes, such as pregnancy and breastfeeding, the biological phenomenon are disarticulated described from their cultural, social and economic dimensions, taken by an instinctive acts, “natural”. The symbolic and material processes, in which the biological phenomena are related and that results in a specific maternity to the group of black women, don’t come up in the textbooks. It was observed continuities in the representation of these group of women: diversity in professional roles, including those associated to science. Although, it is possible to verify these women in care areas, that are social and cultural related to what is feminine. Therefore, it was verified that, despite the fact that there is a big number of black women in biology textbooks, it doesn’t mean that they occupy a singular black woman place, because the images of these women still represent what is universal, not relating them to their history and singularities, their fights, conquers and challenges. The conclusion is that the presence of images of black women in biology textbooks, disarticulated from their socio, historical and cultural place, do not show significative contribution to understand the ethnic-racial relations, once either the biological processes or the images, do not give the possibility to think or problematize the political appropriation of biological knowledge in the definition of the black woman as a subject in Brazilian society.